Highly efficient photocatalytic conversion of CO2 into solid CO using H2O as a reductant over Ag-modified ZnGa2O41. Issue 21 (7th June 2015) - Wang, Zheng; Teramura, Kentaro; Hosokawa, Saburo; Tanaka, Tsunehiro
<x xml:space="preserve">Abstract</x> Highly crystalline ZnGa2O4 modified with Ag particles photocatalytically and selectively converted CO2 into CO (155.0 μmol h−1) using H2O as an electron donor.